Impact evaluation of shamba shape up weather and farming news on smallholder farmers in Kenya - Kiprop, Calvin; Kirwa, Lilian; Ngotho, Elias; Mwungu, Chris; Wanjau, Agnes; Otieno, Felix; Gamoyo, Majambo; Koech, Grace; Ghosh, Aniruddha (2024)
Kenya's agricultural sector plays a crucial role, employing over 75% of the rural population and serving as the catalyst for the other sectors. However, despite its significance, the sector's potential and long-term sustainability are hampered by the negative impacts of climate change. A defining characteristic of Kenyan agriculture is the predominance of smallholder farming systems. These smallholder farmers contend with many challenges that limit their ability to adapt to climate change, including inadequate access to resources and information. Additionally, they often face reduced access to modern technologies and economic limitations that hinder investment in climate-resilient practices. In response to these challenges, Climate Information Services (CIS) have emerged as a potential solution, aiming to equip farmers with actionable climate information to enable informed decision-making. Consequently, innovative programs and media segments have been developed to bridge the information gap and support smallholder farmers. This report presents an impact evaluation of the Shamba Shape Up (SSU) Weather and Farming News segment, focusing on its effectiveness in providing weather-related advisories to smallholder farmers in Kenya to improve farmers’ risk mitigation strategies, institutional capacities, and partnerships. The segment has played a vital role in the broader effort to support smallholder farmers in Kenya, providing them with tailored weather advisories to aid in decision-making. The segment has broadcasted for the last 14 years and is part of the Accelerating Impacts of Consultative Group on International Agricultural Research (CGIAR) Climate Research for Africa (AICCRA) and Climate Resilience (ClimBeR) programs in collaboration with Alliance of Bioversity International and International Center for Tropical Agriculture (ABC). This evaluation aims to quantify the program's impact and understand its reach among the local farming communities in Kenya. The study conducted the evaluation through household surveys across 40 counties in Kenya. The findings revealed that a significant proportion of farmers rely on the SSU Weather News segment for crucial farming decisions, such as when to plant, which crops to plant, where to obtain inputs, seed selection, pest and disease management, soil management and adoption of climate resilient practices. However, the adoption of weather-related risk mitigation measures and sustainable farming practices remains relatively low, indicating the need for increased awareness on such measures to improve resilience among farmers. The report highlights that, according to the sample from the SSU study, SMS was the preferred platform for smallholder farmers in Kenya to receive weather news and agro-advisories. This could be attributed to the platform being the most commonly used by SSU due to its accessibility and immediate delivery. Timely and accurate weather advisories are crucial for effective decision-making, leading to improved crop yields and reduced losses. Aligning advisories with local knowledge and addressing accuracy disparities across counties were identified as key areas for improvement. The report also found that SSU viewers were more likely to adopt sustainable farming practices and employ risk mitigation strategies, resulting in higher agricultural income compared to non-viewers. This demonstrates the significant impact of SSU viewership on decision-making, adoption of climate-resilient agricultural practices, and improved farm outcomes. The economic benefits associated with SSU viewership are significant. For instance, maize farmers who watch SSU report an average income of KES 84,605.46 compared to KES 35,083.28 for non-viewers. Similar trends are observed for beans, Irish potatoes, sweet potatoes, and dairy farming, where viewers achieve higher average incomes and return on investment (RoI). For example, Irish potato farmers who follow SSU news achieve an RoI of 3.34, compared to 1.65 for non-viewers. While these results indicate a correlation between SSU viewership and increased income levels, it is crucial to recognize the potential influence of confounding variables such as farm management practices, resource accessibility, and regional climatic conditions. Variations in farmers' income levels are significantly influenced by disparities in access to high-quality inputs such as seeds, fertilizers, irrigation systems, and farm machinery, as well as the adoption of advanced agricultural practices and technologies. Thus, to establish a causal relationship between SSU viewership and income, additional rigorous analysis is necessary to isolate the independent impact of SSU viewership. Moreover, we used Individual Treatment Effects (ITE) with Causal Forests and Geographically Weighted Regression (GWR) to examine spatial variation, revealing significant differences across counties. Some counties, like Migori, West Pokot, and Makueni, exhibit positive outcomes, while others like Nyandarua and Machakos show negative impacts. Specifically, counties closer to central Kenya (Nyandarua, Nyeri, Murang'a) exhibited lower maximum Individual Treatment Effects (ITEs), whereas Kilifi, Kwale, Migori, West Pokot, Makueni, and Isiolo counties showed higher values, suggesting a potentially greater influence on agricultural revenue in these regions. This underscores the importance of considering location-specific factors when designing interventions. In other words, the unique agricultural, socio-economic, climatic, and cultural factors specific to each geographical location allow sector players to create more effective, targeted, and tailored advisory services. Despite these spatial variations which showed some counties benefiting more from watching SSU weather and farming news, the use of Propensity Score Matching (PSM) showed that, generally, households that watched SSU weather and farming news realized relatively higher incomes. Building on these insights, the evaluation's findings provide valuable guidance for future agricultural development strategies, particularly in the realm of climate advisories. Overall, the findings of the evaluation provide valuable insights for stakeholders involved in agricultural development and climate resilience initiatives in Kenya and beyond. These findings call for continuous improvement in advisory content and delivery to maximize their benefits and strengthen partnerships with relevant organizations to expand outreach and improve advisory services. In addition, the report highlights the importance of addressing disparities within agricultural communities, particularly regarding gender and education, to design effective and inclusive interventions. The adoption of weather-related risk mitigation measures remains low, indicating a need for increased awareness and content. The integration of local knowledge into weather forecasting has emerged as crucial for enhancing advisories. Therefore, gender-sensitive approaches, youth engagement, and continuous improvement in advisory delivery are essential to maximize the impact of SSU and similar advisories on smallholder farmers' livelihoods in Kenya.